Factors influencing industrial carbon emissions and strategies for carbon mitigation in the Yangtze River Delta of China. (20th January 2017) - Xu, Xibao; Yang, Guishan; Tan, Yan; Zhuang, Qianlai; Tang, Xuguang; Zhao, Kaiyan; Wang, Sirui
Abstract: The Yangtze River Delta is one of the most industrialized regions in China. This study characterizes the spatial and temporal patterns of industrial carbon emissions (ICE) produced by secondary industry sectors in the region from 2000 to 2014. The scale and nature of ICE is measured from five aspects (involving 12 factors): gross industrial output value (GIOV), energy intensity (EI), energy structure (ES), industrial structure (IS) and the structure of industrial enterprises (the number and scale). The study establishes three panel models to analyze the effects of 12 factors on ICE at the county level. The results show that ICE increased dramatically, being 2.1 times the 2000 level (135.94 Mt CO2 ) in this region by 2014. The major carbon sources are the consumptions of raw coal and electricity, accounting for more than three quarters of the total ICE during the 2000–2014 period. ICE presents great spatial disparities across 66 counties in the region, being highly coincident with the Z-shaped distribution of the urban clusters in the delta. The GIOV is a major contributor to ICE growth in this region, increasing by 84.1 tC for an increase of one million yuan of GIOV. The adjustment of ES, EI and the structure of industrial enterprises can largely abate ICE. Regulating industrial structure and energy structure, reducing energy intensity and optimizing the structure of industrial enterprises are suggested as imperative measures for carbon mitigation in the region. Highlights: Spatio-temporal patterns of industrial carbon emissions in 2000–2014 were analyzed. GIOV, IS, ES, EI and structure of industrial enterprises were considered. Panel models were built to explore the effects of 12 factors at county level. The GIOV has the largest contributing effects on ICE growth in this region. Adjusting IS, ES, EI and structure of industrial enterprises can largely abate ICE.